2019
DOI: 10.1094/mpmi-05-18-0129-r
|View full text |Cite
|
Sign up to set email alerts
|

Function and Distribution of a Lantipeptide in Strawberry Fusarium Wilt Disease–Suppressive Soils

Abstract: Streptomyces griseus S4-7 is representative of strains responsible for the specific soil suppressiveness of Fusarium wilt of strawberry caused by Fusarium oxysporum f. sp. fragariae. Members of the genus Streptomyces secrete diverse secondary metabolites including lantipeptides, heat-stable lanthionine-containing compounds that can exhibit antibiotic activity. In this study, a class II lantipeptide provisionally named grisin, of previously unknown biological function, was shown to inhibit F. oxysporum. The inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…3c). The population of SP6C4 was determined by qPCR with primers for the SP6C4-speci c lanM lantipeptide biosynthesis gene [39]. On owers sprayed with L-glutamic acid, the density of SP6C4 was greater than 10 5 copy/g of ower, but lanM gene copies at 8 weeks on the untreated control and those sprayed with L-asparagine had fewer than10 4 copy/g of ower (Additional le 1: Figure S4g).…”
Section: Glutamic Acid Restructured the Anthosphere Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…3c). The population of SP6C4 was determined by qPCR with primers for the SP6C4-speci c lanM lantipeptide biosynthesis gene [39]. On owers sprayed with L-glutamic acid, the density of SP6C4 was greater than 10 5 copy/g of ower, but lanM gene copies at 8 weeks on the untreated control and those sprayed with L-asparagine had fewer than10 4 copy/g of ower (Additional le 1: Figure S4g).…”
Section: Glutamic Acid Restructured the Anthosphere Microbiomementioning
confidence: 99%
“…To determine whether the population size of the core microbe S. globisporus SP6C4 increased in response to the amino acid treatments, microbial DNA from the ower anthosphere was extracted and the SP6C4-speci c marker gene lanM was quanti ed by qPCR with F and R primers as described by Kim et al [39]. qPCR reactions in SYBR Green ® TOYOBO master mix included denaturation at 98°C for 5 min followed by 40 cycles of denaturation at 98°C for 30 sec, annealing at 59°C for 30 sec and elongation at 72°C for 45 sec with a CFX Connect™ Optics Module Real-Time PCR System (Bio-Rad, Hercules, CA, USA).…”
Section: Disease Incidence Of Gray Mold and Blossom Blight And Qpcr Omentioning
confidence: 99%
“…Strain S4‐7 was selected based on community DNA analyses and phenotypic characteristics that revealed an enrichment of actinobacterial sequences in the suppressive soil, slow growth, and tolerance to moderate heat. The strain inhibited F. oxysporum in vitro , suppressed disease on strawberry, and produced a novel heat‐stable, ribosomally synthesized thiopeptide, conprimycin, a major factor in control of the pathogen that, based on chemogenomic analysis, interfered with cell wall organization and biogenesis, transcription, cytoskeleton organization, and RNA catabolism in the model yeast Saccharomyces cerevisiae . Further genetic dissection of the antifungal arsenal of S4‐7 has revealed that within its genome are 30 predicted secondary metabolite gene clusters including four lantipeptides, two bacteriocins, two siderophores, two butyrolactones, three NRPSs, six clusters encoding terpenes, two ectoines, three polyketide synthetases, four NRPSs linked to polyketide synthetases, one melanine cluster, and a lassopeptide cluster .…”
Section: Streptomyces: Long Sought Newly Recognized As ‘Plants’ Bestmentioning
confidence: 99%
“…Of these, the ribosomally synthesized and posttranslationally modified LanM lanthipeptide provisionally named grisin, contributed substantially to inhibition of the wilt pathogen and is the first class II lantipeptide from Streptomyces reported to have a biological function. In addition, the lanM gene itself has proven useful as a molecular probe for the presence in soils of populations of Streptomyces capable of mediating soil suppressiveness of the Fusarium wilt pathogen . Strain S4‐7 also produces three volatile terpenes, geosmin, caryolan‐1‐ol, and an unknown sesquiterpene, with caryolan‐1‐ol responsible for dose‐dependent inhibition of growth and sporulation of the strawberry foliar pathogen Botrytis cinerea .…”
Section: Streptomyces: Long Sought Newly Recognized As ‘Plants’ Bestmentioning
confidence: 99%
“…More investigations have recently focused on the comparative analyses of the microbial community between the conducive and suppressive soils, and the identification of key indicators that participate in disease suppression [4,8]. In fact, unique soil situations lead to differential changes of microbial community, thereby contributing to variation in the ability of soils to suppress soil-borne pathogens [7,15,19,20].…”
Section: Introductionmentioning
confidence: 99%